Performance of music elevates pain threshold and positive affect: implications for the evolutionary function of music. - Dunbar, R; Kaskatis, K; MacDonald, I; Barra, V (2012)
It is well known that music arouses emotional responses. In addition, it has long been thought to play an important role in creating a sense of community, especially in small scale societies. One mechanism by which it might do this is through the endorphin system, and there is evidence to support this claim. Using pain threshold as an assay for CNS endorphin release, we ask whether it is the auditory perception of music that triggers this effect or the active performance of music. We show that singing, dancing and drumming all trigger endorphin release (indexed by an increase in post-activity pain tolerance) in contexts where merely listening to music and low energy musical activities do not. We also confirm that music performance results in elevated positive (but not negative) affect. We conclude that it is the active performance of music that generates the endorphin high, not the music itself. We discuss the implications of this in the context of community bonding mechanisms that commonly involve dance and music-making.